2011
DOI: 10.1021/jm2007886
|View full text |Cite
|
Sign up to set email alerts
|

New Serotonin 5-HT1A Receptor Agonists with Neuroprotective Effect against Ischemic Cell Damage

Abstract: We report the synthesis of new compounds 4− 35 based on structural modifications of different moieties of previously described lead UCM-2550. The new nonpiperazine derivatives, representing second-generation agonists, were assessed for binding affinity, selectivity, and functional activity at the 5-HT 1A receptor (5-HT 1A R). Computational β 2 -based homology models of the ligand−receptor complexes were used to explain the observed structure−affinity relationships. Selected candidates were also evaluated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…A possible interpretation for these results could lie on the fact that Neu-P11 also interacts with 5-HT1A/1D receptors (15). It has been reported that different 5HT1A agonists are able to attenuate excitotoxicity, proving neuroprotective in global and focal ischemia animal models (36). Furthermore, some 5HT1A…”
Section: Discussionmentioning
confidence: 96%
“…A possible interpretation for these results could lie on the fact that Neu-P11 also interacts with 5-HT1A/1D receptors (15). It has been reported that different 5HT1A agonists are able to attenuate excitotoxicity, proving neuroprotective in global and focal ischemia animal models (36). Furthermore, some 5HT1A…”
Section: Discussionmentioning
confidence: 96%
“…These effects were blocked by WAY 100635 (5-HT 1A receptor antagonist), thereby confirming the neuroprotective properties of 5-HT 1A receptors [164]. Marco et al ., (2011) reported that a high-affinity and potent 5-HT 1A R agonist (2-{6-[(3,4-dihydro-2H-chromen-2-ylmethyl)amino]hexyl}-tetrahydro-1Hpyrrolo [1,2c]imidazole-1,3(2H)-dione) exhibits neuroprotective effect, which was validated using neurotoxicity assays in primary cell cultures from rat hippocampus and in the MCAO model of focal cerebral ischemia in rats [165]. Li et al ., (2010) recited neuroprotective effect of fluoxetine against 3,4-methylenedioxymethamphetamine (MDMA) induced reduction in serotonin transporter (SERT; a reliable marker for accessing the integrity of serotonergic neurons) in rat brain as examined with N,N-dimethyl-2-(2-amino-4-[18F]-fluorophenylthio) benzylamine (4-[18F]-ADAM; a SERT radioligand) and micro positron emission tomography (micro-PET) analysis.…”
Section: Serotoninmentioning
confidence: 99%
“…The homology models explained binding modes and subtype selectivity among these receptors for a diverse set of AR antagonists. Other very effective homology models were used to rationalize agonist activities at the serotonin 5HT 1A receptor [95] and the somatostatin receptor subtype 4 [39], the activity of nucleosides at the A1 and A3 receptors [96,97], and inverse agonism/antagonism versus partial/full agonism activities of b 2 AR ligands [98,99]. Constructed from the dopamine D3 receptor X-ray structure as a template, D3R and D2R homology models were refined by molecular dynamics to guide in the design of highly D3R-selective ligands with desired efficacies [100].…”
Section: Computational Drug-discovery Studiesmentioning
confidence: 99%